2004
DOI: 10.1016/j.febslet.2004.07.091
|View full text |Cite
|
Sign up to set email alerts
|

Wheat pathogenesis‐related proteins of class 4 have ribonuclease activity

Abstract: We have demonstrated that wheatwin1, a wheat pathogenesis-related protein of class 4 (PR4), has ribonuclease activity. Both native and recombinant proteins hydrolyse RNA from wheat coleoptils and have antifungal activity. Sepharosebound wheatwin1 is able to interact with either wheat or Fusarium culmorum RNA. 3D modelling studies showed that, like ribonucleases A and T1, the action mechanism should involve two His residues, an Arg residue and an Asp residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 26 publications
2
62
0
2
Order By: Relevance
“…The content of soluble, insoluble and total protein in the shoots showed an increase in wheat plants inoculated with all the Fusarium species (Fig. 5), as also recorded by other authors (Carporale et al, 2004;Przymusinski et al, 2004), who indicated that plants respond to pathogens by defence strategies leading to the synthesis of protective compounds such as pathogenesis-related proteins. Even though 100 different proteins from the PR-10 family have been identified, their biological function has not yet been clarified and most of the roles suggested are highly hypothetical.…”
Section: Metabolic Activitysupporting
confidence: 84%
“…The content of soluble, insoluble and total protein in the shoots showed an increase in wheat plants inoculated with all the Fusarium species (Fig. 5), as also recorded by other authors (Carporale et al, 2004;Przymusinski et al, 2004), who indicated that plants respond to pathogens by defence strategies leading to the synthesis of protective compounds such as pathogenesis-related proteins. Even though 100 different proteins from the PR-10 family have been identified, their biological function has not yet been clarified and most of the roles suggested are highly hypothetical.…”
Section: Metabolic Activitysupporting
confidence: 84%
“…A few PRs families have enzymatic effects such as chitinases (PR-3, PR-8, PR-11) 105,168 , glucanases (PR-2) 136,137 , peroxidases (PR-9) 2,132,331 , ribonucleases (PR-10) 85,190 and (PR-4) 41 , or inhibitory effects such as enzyme inhibitors (PR-6) 326,349 . Inhibitory activity towards proteases or α-amylases is ascribed to the PR-5 298 , PR-12 192 and PR-14 family 160,161 .…”
Section: Biological Function and Mechanism Of Actionmentioning
confidence: 99%
“…Binding of the PR-4 members with the chitin-binding domain to chitin in the developing fungal cell walls might result in fungal growth retardation. Ribonuclease activity of some cereal seed PR-4 has been observed and the effect on the invading microorganisms explained alternatively as inhibition of the translation process 41 .…”
Section: Barwin (Barley Wound Induced Protein) (Pr-4)mentioning
confidence: 99%
“…Data were processed as described previously 37 . Briefly, sequences were quality filtered and dereplicated using the QIIME script split_libraries.py with the homopolymer filter deactivated 38 , checked for chimeras against the GreenGenes database (October 2013 release) using UCHIME ver.…”
Section: Processing Of Sequence Datamentioning
confidence: 99%
“…36 PR4 proteins show antifungal activity against several phytopathogenic fungi and have been demonstrated to possess ribonucleasic activity correlated to their antifungal capacity. 37,38 PR5 encodes a thaumatin-like protein which exhibits antifungal activity against snow mold and Microdochium nivale. In shoots, PR5 (WAS-3a) was induced by 2.1-fold at 72 h post MeJA treatment ( Fig.2; Supplementary Fig.S1(f)).…”
Section: Pathogenesis-related Genesmentioning
confidence: 99%